Print Quarterly - Landau, David (London : Print Quarterly Publications, 1984)
Print Quarterly is the leading international journal dedicated to the art of the print from its origins to the present, covering printmaking traditions all across the globe. The journal publishes recent scholarship on a wide range of topics, including printmakers, iconography, social and cultural history, popular culture, print collecting, book illustration, decorative prints, and techniques such as engraving, etching, woodcutting, lithography and digital printmaking (https://printquarterly.co.uk/)
Https://printquarterly.co.uk/ (registers)
Online: https://www.jstor.org/journal/printquarterly (login)
Engels
Tijdschriften